1995
DOI: 10.1002/aja.1002020406
|View full text |Cite
|
Sign up to set email alerts
|

Muscle cell death during the development of head and neck muscles in the chick embryo

Abstract: Degenerating myofibers have been reported in the embryos and neonates of a number of birds and mammals, but neither the pervasiveness of the phenomenon nor the spatiotemporal patterns of degeneration has been examined in detail. Using transmission electron microscopy, we determined the patterns of muscle cell death in the chick biventer cervicis, a head extensor muscle. Cell death is most pronounced at incubation days 10 through 15, and occurs throughout the muscle. This is the period during which many myofibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…54 Apoptotic muscle cells have been described during skeletal muscle development. 55 We observed apoptotic myoblasts during early development of striated muscle characterized by migration and fusion of the myoblasts to form myotubes. In the day 7.5 embryonic limb apoptotic myoblasts were scattered in developing leg and thigh skeletal muscle.…”
Section: Discussion Induction Of Transglutaminase In Apoptosismentioning
confidence: 93%
“…54 Apoptotic muscle cells have been described during skeletal muscle development. 55 We observed apoptotic myoblasts during early development of striated muscle characterized by migration and fusion of the myoblasts to form myotubes. In the day 7.5 embryonic limb apoptotic myoblasts were scattered in developing leg and thigh skeletal muscle.…”
Section: Discussion Induction Of Transglutaminase In Apoptosismentioning
confidence: 93%
“…Though we cannot substantiate, for certain, the role of R-Ras in myogenesis in vivo at the present stage, one can assume that R-Ras may prevent cell death and stimulate locomotion on muscle dierentiation during embryogenesis and tissue regeneration. It has been reported that myogenesis is accompanied by cell death of myoblasts in vivo (McClearn et al, 1995). R-Ras thus may maintain survival of muscle precursor cells, which are more sensitive to apoptosis than terminally dierentiated myotubes, during myogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Chen et al (2006) found morphological changes of the skeletal muscle, tendon, and periosteum in senescence-accelerated mice (SAMP6) compared to age-matched normal SAMR1 mice. McClearn et al (1995) explored the pervasiveness of myofiber degeneration and spatiotemporal patterns of degeneration during the development of head and neck muscles in chick embryos by evaluating morphological characteristics of muscle cells. In duck, Li et al (2010) compared morphological characteristics of pectoral and leg muscle tissues during duck embryo stages to the neonatal stage through paraffin sections.…”
Section: Discussionmentioning
confidence: 99%